Answer: Triangle QRS is an isosceles triangle because QR = RS.
. Step-by-step explanation: Find the length of each side of the triangle using the formula for calculating the distance between two points.
Step-by-step explanation:
Answer:
1. (x - 3)² = 8
2. (x + 2)² = 3
3. (x + 6)² = ![$ \frac{101}{2} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B101%7D%7B2%7D%20%24)
4. (x + 3)² = 27
5. (x + 4)² = 13
6. ![$ \bigg( x - \frac{15}{9} \bigg) ^2 = \frac{261}{81} = \frac{29}{9} $](https://tex.z-dn.net/?f=%24%20%5Cbigg%28%20x%20-%20%5Cfrac%7B15%7D%7B9%7D%20%5Cbigg%29%20%5E2%20%3D%20%5Cfrac%7B261%7D%7B81%7D%20%3D%20%5Cfrac%7B29%7D%7B9%7D%20%24)
Step-by-step explanation:
Completion of Square: ![$ (x - a) ^2 = x^2 - 2ax + a^2 $](https://tex.z-dn.net/?f=%24%20%28x%20-%20a%29%20%5E2%20%3D%20x%5E2%20-%202ax%20%2B%20a%5E2%20%24)
In the following problems the terms in the RHS of the above equation may be missing. We balance the equation. Simplify it and re write it in terms of LHS.
1. x² - 6x + 1 = 0
Taking the constant term to the other side, we get:
x² - 6x = - 1
⇒ x² - 2(3)x = -1
⇒ x² -2(3)x + 9 = - 1 + 9 [Adding 9 to both the sides]
⇒ x² -2(3)x + 3² = 8
⇒ (x - 3)² = 8 is the answer.
2. 3x² + 12x + 3 = 0
Note that the co-effecient of x² is not 1. We make it 1, by dividing the whole equation by 3. And then proceed like the previous problem.
3x² + 12x = -3
Dividing by 3 through out, x² + 4x = - 1
⇒ x² + 2(2) + 4 = -1 + 4
⇒ x² +2(2) + 2² = 3
⇒ (x + 2)² = 3 is the answer.
3. 2x² + 24x = 29
x² + 12x = ![$ \frac{29}{2} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B29%7D%7B2%7D%20%24)
⇒ x² + 2(6)x + 36 =
+ 36
⇒ x² + 2(6)x + 6² = ![$ \frac{29 + 72}{2} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B29%20%2B%2072%7D%7B2%7D%20%24)
⇒ (x + 6)² =
is the answer.
4. x² + 6x - 18 = 0
x² + 6x = 18
⇒ x² + 2(3)x = 18
⇒ x² + 2(3)x + 9 = 18 + 9
⇒ x² + 2(3)x + 3² = 27
⇒ (x + 3)² = 27 is the answer.
5. x² + 8x + 3 = 0
x² + 8x = -3
⇒ x² + 2(4)x = -3
⇒ x² + 2(4)x + 16 = - 3 + 16
⇒ x² + 2(4)x + 16 = 13
⇒ (x + 4)² = 13 is the answer.
6. 9x² - 30x + 6 = 0
9x² - 30x = - 6
⇒ x²
x = - 6
![$ \implies x^2 -2 \bigg( \frac{15}{9} \bigg )x + \frac{225}{81} = - 6 + \frac{225}{81} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20x%5E2%20-2%20%5Cbigg%28%20%5Cfrac%7B15%7D%7B9%7D%20%5Cbigg%20%29x%20%2B%20%5Cfrac%7B225%7D%7B81%7D%20%3D%20-%206%20%2B%20%5Cfrac%7B225%7D%7B81%7D%20%24)
![$ \implies x^2 - 2\bigg( \frac{15}{9} \bigg ) x + \bigg ( \frac{15}{9} \bigg ) ^2 = \frac{261}{81} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20x%5E2%20-%202%5Cbigg%28%20%5Cfrac%7B15%7D%7B9%7D%20%5Cbigg%20%29%20x%20%2B%20%5Cbigg%20%28%20%5Cfrac%7B15%7D%7B9%7D%20%5Cbigg%20%29%20%5E2%20%3D%20%5Cfrac%7B261%7D%7B81%7D%20%24)
is the answer.
3: terms/ 12, 8r, -3, s, -5, 15t coefficients/ 8r, 1s, 15t
Answer: A. Factor 2 => 4x greater
Factor 3 => 9x greater
Factor 5 => 25x greater
Step-by-step explanation: A. A cylinder is formed by 2 circles and a rectangle in the middle. That's why surface area is given by circumference of a circle, which is the length of the rectangle times height of the rectangle, i.e.:
A = 2.π.r.h
A cylinder of radius r and height h has area:
= 2πrh
If multiply both dimensions <u>by a factor of 2</u>:
= 2.π.2r.2h
= 8πrh
Comparing
to
:
=
= 4
Doubling radius and height creates a surface area of a cylinder 4 times greater.
<u>By factor 3:</u>
![A_{3} = 2.\pi.3r.3h](https://tex.z-dn.net/?f=A_%7B3%7D%20%3D%202.%5Cpi.3r.3h)
![A_{3} = 18.\pi.r.h](https://tex.z-dn.net/?f=A_%7B3%7D%20%3D%2018.%5Cpi.r.h)
Comparing areas:
=
= 9
Multiplying by 3, gives an area 9 times bigger.
<u>By factor 5</u>:
![A_{5} = 2.\pi.5r.5h](https://tex.z-dn.net/?f=A_%7B5%7D%20%3D%202.%5Cpi.5r.5h)
![A_{5} = 50.\pi.r.h](https://tex.z-dn.net/?f=A_%7B5%7D%20%3D%2050.%5Cpi.r.h)
Comparing:
=
= 25
The new area is 25 times greater.
B. By analysing how many times greater and the factor that the dimensions are multiplied, you can notice the increase in area is factor². For example, when multiplied by a factor of 2, the new area is 4 times greater.
Given that the score of the student on the quiz was 25c - 10(15 - c)
It can be seen that the first term of expression for her score (i.e. 25c) shows that 25 marks were awarded to each correct answer.
The second term of the expression (i.e. 10(15 - c)) represent that 10 marks were deducted from each wrong answer.
Thus, the number of wrong answers is 15 - c.
The sum of the correct answers and the wrong answers gives the total number of questions in the quiz.
Thus, the total number of questions in the quiz is given by 15 - c + c = 15.
Therefore, there are 15 questions in the quiz.